Fatal breakthrough infection with Fusarium andiyazi: new multi‐resistant aetiological agent cross‐reacting with Aspergillus galactomannan enzyme immunoassay. Issue 4 (6th October 2013) - Kebabcı, Nesrin; van, Anne D.; Ener, Beyza; Ersal, Tuba; Meijer, Martin; Al‐Hatmi, Abdullah M.S.; Özkocaman, Vildan; Ursavaş, Ahmet; Çetinoğlu, Ezgi D.; Akalın, Halis
Summary Disseminated infections caused by members of the Fusarium fujikuroi species complex (FFSC) occur regularly in immunocompromised patients. Here, we present the first human case caused by FFSC‐member Fusarium andiyazi. Fever, respiratory symptoms and abnormal computerised tomography findings developed in a 65‐year‐old man with acute myelogenous leukaemia who was under posaconazole prophylaxis during his remission–induction chemotherapy. During the course of infection, two consecutive blood galactomannan values were found to be positive, and two blood cultures yielded strains resembling Fusarium species, according to morphological appearance. The aetiological agent proved to be F. andiyazi based on multilocus sequence typing. The sequencing of the internal transcribed spacer region did not resolve the closely related members of the FFSC, but additional data on partial sequence of transcription elongation factor 1 alpha subunit did. A detailed morphological study confirmed the identification of F. andiyazi, which had previously only been reported as a plant pathogen affecting various food crops.